Kitab Riwayah Isra Mikraj dan Kontekstualisasi Makna Isra Mikraj - Reseta Dewi, Sintia Yuliani; Khusniyah, Aziizatul (PERADA, 2025)
The Qur'an, as a miracle of Prophet Muhammad SAW, contains various aspects of life, one of which is the event of Isra and Mi'raj, recorded in QS. Al-Isra, verse 1. This event describes the miraculous journey of Prophet Muhammad from Masjid al-Haram to Masjid al-Aqsa and Sidrat al-Muntaha, marking the beginning of the obligation of the five daily prayers. This study focuses on the philological analysis of the manuscript Riwayah Isra Mi'raj by K.H. Ahmad Fauzan, which reflects nationalist values and illustrates the integration of Islam with socio-political contexts. Using a codicological approach, this research examines the history of the manuscript, its physical condition, and the content related to the verse of Al-Isra, in order to uncover the wisdom of the Isra Mi'raj event from a philological perspective. This study aims to contribute to a deeper understanding of Islamic history and teachings, while enriching the field of philological studies in the context of Islam.